Gambaran Self Stigma Penderita HIV/AIDS di Poli Cendana Rumah Sakit Ngudi Waluyo Wlingi - Endah Tri Suryani (Journal of Ners and Midwifery, 2016)
The spread of HIV and AIDS in Indonesia over the last five years is quite high. United Nations AIDS (UNAIDS) even dub Indonesia as an Asia’s country with most spread of HIV/AIDS. However the fear of stigma and discrimination against PLWHA (people living with HIV/AIDS) remains a major obstacle. The purpose of this research was to describe self stigma of HIV/AIDS in poly Cendana Ngudi Waluyo Hospital Wlingi based questionnaire ISMI (Internalized Stigma of Mental Illness) that included a portrait of alienation, acceptance of stereotypes, experience of discrimination, social withdrawal, and rejection of stigma. The samples were 27 people with HIV/AIDS. The results showed that generally self stigma of HIV/AIDS were low 44.4% (12 patients). This result, indicated that the motivation of people living with HIV/AIDS as well as their moral support was instrumental in lowering self-stigma. Recommendations from this study were expected for health care to prevent and overcome self stigma of HIV/AIDS.